2007
DOI: 10.1103/physrevlett.98.206101
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Row Doubling in the STM Images of Cu(014)-O Obtained with MnNi Tips

Abstract: We report on scanning tunneling microscopy studies of the Cu(014)-O surface using MnNi tips. Remarkably, the results show a regular apparent doubling of surface atomic rows in the f110g direction. A qualitative explanation of this feature based on tight binding and density functional theory calculations of the electronic structure of the tip is presented. Double imaging of the same atom by different legs of d yz orbital could be the reason for the observed doubling. The orientation of the orbital is determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
(30 reference statements)
1
19
0
Order By: Relevance
“…Therefore the non-perturbative approach is required to find the dependence of the tunneling current from the tip-surface distance. It has also been demonstrated recently that the orbital structure of a metallic probe can induce unusual electronic effects on a subatomic scale [8,9,[18][19][20], which can complicate the explanation of experimental atomically resolved images. For this reason light element-terminated probes with spatially localized atomic orbitals at the apex which have a 2 minimal number of electron states involved in the tunneling can provide enhanced spatial resolution in STM experiments [21,22] and simplify the interpretation of atomically resolved STM data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore the non-perturbative approach is required to find the dependence of the tunneling current from the tip-surface distance. It has also been demonstrated recently that the orbital structure of a metallic probe can induce unusual electronic effects on a subatomic scale [8,9,[18][19][20], which can complicate the explanation of experimental atomically resolved images. For this reason light element-terminated probes with spatially localized atomic orbitals at the apex which have a 2 minimal number of electron states involved in the tunneling can provide enhanced spatial resolution in STM experiments [21,22] and simplify the interpretation of atomically resolved STM data.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the electronic structure of the tip apex atom plays a key role in STM tunneling [1][2][3]. Particularly, for some tipsample systems an agreement between experiment and simulation could only be obtained by including the fine tip electronic structure in calculations [4][5][6][7][8][9]. It is known that the electronic structure of a realistic tip is usually determined by a mixture of s-, p-and dstates while the local density of states (LDOS) near the Fermi level can be highly dependent on the energy of tunneling electrons [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, even the simplest situations shown in Fig. 15.2 can be realized in STM experiments [26,34].…”
Section: Basic Principle and Experimental Realization Of Stmmentioning
confidence: 97%
“…Our experiments showed that eight features along the ͓110͔ direction could be resolved for certain tunneling conditions at different scan rates and fast scan axis directions. 37 The splitting of atomic features along the ͓110͔ direction was observed less often than along the ͓110͔ one and was not so well resolved. Typically, the images with subtle subatomic structure appeared after a series of bias voltage pulses ͑4 -4.5 V͒ producing a suitable MnNi apex.…”
Section: Cu(014)-omentioning
confidence: 99%